Edukasi Pentingnya Pandai Berbicara di Depan Umum pada Siswa Kelas 12 Di Smk Darussalam Cilacap - Hidayat Nurseptiadi; Dwi Setiawan; Rika Puji Lestari (Jurnal DIKMAS, 2021)
Public speaking skills are one of the most important soft skills in various aspects of life. This study aims to find out how far 12th-grade students at SMK Darussalam Cilacap understand the importance of these skills and how educationals programs can improve their abilities. Through this study, is expected to be a reference for schools in developing similar programs and improving the quality of graduates.